Autotaxin is a valuable biomarker for the prediction of liver fibrosis in patients with non‐alcoholic fatty liver disease. Issue 10 (4th July 2019) - Honda, Yasushi; Imajo, Kento; Kobayashi, Takashi; Kessoku, Takaomi; Ogawa, Yuji; Tomeno, Wataru; Yoneda, Masato; Kobayashi, Noritoshi; Saito, Satoru; Nakajima, Atsushi
Abstract : Aim: We investigated the characteristics of serum autotaxin (ATX) and its diagnostic performance for liver fibrosis in a large cohort of patients with non‐alcoholic fatty liver disease (NAFLD). Methods: We compared the usefulness of ATX and other fibrosis markers in 307 biopsy‐confirmed NAFLD patients. In addition, in 145 participants with NAFLD, we compared the diagnostic performance of ATX with that of non‐invasive imaging methods (vibration‐controlled transient elastography and magnetic resonance elastography [MRE]). Results: Serum ATX concentration was significantly correlated with fibrosis stage in male and female NAFLD patients. In male patients, the area under the receiver operating characteristic (AUROC) curve values of ATX for the diagnosis of ≥stage 1, ≥stage 2, ≥stage 3, and ≥stage 4 fibrosis were 0.65, 0.75, 0.81, and 0.95, respectively. In female NAFLD participants, the AUROC values were all >0.81. The sensitivity of ATX was highest for the diagnosis of ≥stage 2 and ≥stage 3 fibrosis in both men and women with NAFLD. In the comparison between ATX and non‐invasive imaging methods, the AUROC for MRE was the highest at every stage of fibrosis. Conclusions: Serum ATX concentration is significantly correlated with fibrosis stage in NAFLD patients. The diagnostic accuracy of ATX for liver fibrosis is lower than that of MRE, but the sensitivities of ATX for the diagnosis of ≥stage 2 and ≥stage 3 were highest. We conclude that ATX is useful for the selection of patients requiring further evaluation for liver fibrosis.